MAKANAN TABU DI BANJAR JAWA BARAT - Dadang Sukandar (Jurnal Gizi dan Pangan, 2006)
Food taboo in Indonesia is still a problem because there  are many taboo foods.  As consequences,  pregnant mother, lactating mother and children  do not eat the taboo foods so that it can reduce their food intake and finally it can decrease their nutritional status.   Objectives of this study are  1) to identify taboo foods and 2) to identify reasons of taboo foods and  3) to improve basic nutrition knowledge through training  on food and nutrition.  Study was conducted in Banjar West Java from December 2005 to November 2006.  A sample size 92 households was drawn randomly from household population of size 482. The household of population is farmer household who are beneficiary of Special Program for Food Security, Food and Agriculture Organization. Data were analyzed quantitatively and qualitatively and presented in one way table. Results show that groups which had a large number of food taboo were pregnant women group and lactating mother group. There are 35 taboo foods for pregnant women and 24  taboo foods for lactating mother. Some taboo foods for pregnant women are ambon banana, bee, bee egg, cat fish, coconut plus red sugar, eel, coffee, bogo fish, fishing fish, gabus fish, gnetum gnemon and its leaf, ice, jack fruit, kind of jack fruit (kulur), kind of leaf (leaf of so), etc.  Some  taboo foods for lactating mother are banana, bean sprout, beverage made with such droplets, cucumber, eel, egg, fat food, fish, hot food, ice, innards of gurami, jack fruit, kind of cake (serabi), kind of fruit (kulur), kind of jack fruit (sukun), etc. After attending training, the knowledge on nutrition and food of the farmers increase significantly, therefore it is hoped  that their knowledge can reduce their believe of the food taboo.